2013
DOI: 10.1186/2045-8118-10-4
|View full text |Cite
|
Sign up to set email alerts
|

Method for isolation and molecular characterization of extracellular microvesicles released from brain endothelial cells

Abstract: BackgroundIn addition to possessing intracellular vesicles, eukaryotic cells also produce extracellular microvesicles, ranging from 50 to 1000 nm in diameter that are released or shed into the microenvironment under physiological and pathological conditions. These membranous extracellular organelles include both exosomes (originating from internal vesicles of endosomes) and ectosomes (originating from direct budding/shedding of plasma membranes). Extracellular microvesicles contain cell-specific collections of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
156
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(159 citation statements)
references
References 37 publications
3
156
0
Order By: Relevance
“…In the brain, exosomes from cultured glioblastoma cells induce angiogenesis by delivering their contents of proangiogenic proteins, mRNAs, and miRNAs into cerebral endothelial cells (68). Additionally, immortalized human brain microvascular endothelial cells secrete exosomes (69). Proteomic analysis has demonstrated that exosomes released by human cerebral endothelial cells contain 1,179 proteins, including several receptors that carry macromolecules across the BBB, such as transferrin receptor and insulin receptor (69).…”
Section: Exosomes and Cerebral Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…In the brain, exosomes from cultured glioblastoma cells induce angiogenesis by delivering their contents of proangiogenic proteins, mRNAs, and miRNAs into cerebral endothelial cells (68). Additionally, immortalized human brain microvascular endothelial cells secrete exosomes (69). Proteomic analysis has demonstrated that exosomes released by human cerebral endothelial cells contain 1,179 proteins, including several receptors that carry macromolecules across the BBB, such as transferrin receptor and insulin receptor (69).…”
Section: Exosomes and Cerebral Angiogenesismentioning
confidence: 99%
“…Additionally, immortalized human brain microvascular endothelial cells secrete exosomes (69). Proteomic analysis has demonstrated that exosomes released by human cerebral endothelial cells contain 1,179 proteins, including several receptors that carry macromolecules across the BBB, such as transferrin receptor and insulin receptor (69). The role of these exosomal proteins has not been investigated, but interactions between cerebral endothelial exosomes and pericytes have been studied (70).…”
Section: Exosomes and Cerebral Angiogenesismentioning
confidence: 99%
“…A possible fundamental role could be played by extracellular vesicles called endothelial microparticles (EMPs) released from the brain endothelial cells lining capillaries and forming part of the blood -brain barrier for the bidirectional brain-body connections [83]. Brain endothelial cell extracellular vesicles can externalize brain-specific biomarkers into the blood stream and, via transcytosis, allow the migration of blood-borne molecules into the brain [86,87]. They are present in the circulation and are increased in infectious and thrombotic states indicating an involvement in such states [87,88].…”
Section: (C) Central Nervous Systemmentioning
confidence: 99%
“…[9][10][11][12] However, only a few were used for drug or short-nucleic-acid delivery. [13][14][15][16][17] We hereby presented the isolation and function characterization of exosomes from endothelial cells to deliver siRNA to endothelial cells.…”
Section: Discussionmentioning
confidence: 99%